Pemberdayaan masyarakat melalui pelatihan pembuatan pupuk organik menggunakan tabung fermentasi berbasis teknologi di Desa Ulugalung Kabupaten Bantaeng - Muhammad Nur Jumadil; Widya Astuti Rinduwati; Ainun Septia Nengsi Ramli; Andi Izdihar Sricendani; Andi Maulidyisah Ekasalim; Nunik Lestari (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2021)
Ulugalung Village, which is located in Bantaeng Regency, often experiences fertilizer scarcity problems. On the other hand, natural resources in the form of rice straw are very abundant there. However, the community does not have adequate knowledge and skills to process rice straw into organic fertilizer. Therefore, training is needed to help the community overcome these problems. The purpose of this community service activity is to improve the knowledge and skills of the community in Ulugalung Village in making organic fertilizer by utilizing a technology-based fermentation tube composter. This activity combines the lecture method in delivering training materials, as well as a demonstration method to provide skills and experience in making organic fertilizers made from rice straw waste. This activity involved academics, the government, the Pullauweng farmer group, and the Ulugalung villagers. The results of this activity show that the level of achievement of the goals of this service activity is very good, with an increase in the knowledge and skills of participants by 87.7%. This percentage indicates that participants understand the knowledge related to straw composting and can practice the process of composting rice straw using technology-based fermentation tubes independently.